(1/2,1/2)-Fuzzy QS–ideals and its correlation coefficients - Mostafa Hassan; Samy Mostafa (Journal of Hyperstructures)
As an extension of intuitionistic fuzzy sets, we introduce the notion of -fuzzy set ( denoted by SSR) of QS -ideals on a OS -algebra and investigate its properties. Furthermore we study the homomorphic image and inverse image of SSR -fuzzy QS -ideals of a QS -algebra under homomorphism of QS -algebras. Moreover, the Cartesian product of SSR -fuzzy QS -ideals in Cartesian product QS-algebras is given. Finally, novel correlation coefficient between two SSR- fuzzy sets are also studied.